Metaphorical representation of time in the Russian and Tuvan language picture of the world - Arsenyeva, Irina A.; Kuular, Elena M. (The New Research of Tuva, 2024)
The article presents a comparative analysis of the linguistic means used to express the metaphorical representation of the concept of time in Russian and Tuvan. The aim of the study is to identify the characteristics of the metaphorical expression of time through the inflectional system of the Russian language and agglutinative structure of the Tuvan language. The study focuses on metaphorical phrases containing the words “vremya” ‘time’, “yie” ‘time’, “shag” and “shak” ‘hour’, and lexical sources were used as the basis for the analysis. Lexicographical and componential analysis techniques were applied. Two models of time are discussed: a model directly related to time itself (the Time Flow model), and a human-oriented model (the Human Path model). The peculiarities of how certain expressions with the words “vremya” ‘time’, “yie” ‘time’, “shag” and “shak” ‘hour’, are divided into different meanings in different typologically different languages is noted. It is revealed how the same mental content can be conveyed by various linguistic means, such as event-inflected Russian and static agglutinative Tuvan. The similarities in the way time are expressed in language are due to the existence of universal metaphorical models in both linguistic representations of the world. In both languages, time is seen as movement, irreversible movement, and movement at different speeds. In Russian, time is usually expressed with the help of verbs or phrases, while in Tuvan it is often expressed through phrases containing nouns, adjectives, and verbs. These differences in expression reflect the unique ways that each language conceptualizes time.